Aspect of Bobwhite Quail Mobility During Spring Through Fall Months - David Urban (National Quail Symposium Proceedings, 2017)
The mobility of bobwhite quail was studied on an 1160-acre nonhunted area in southern Illinois during March through November. Seventy-eight quail (39 adult males, 29 adult females and 9 young of the year) were radio instrumented. Radio locations totaled 2,302 during 1,726 days in which quail were radio marked. Increase in average monthly range from March to April was attributed to change in habitat preference. Considerable variation in monthly ranges during the period of June through August were noted and attributed to variations in breeding status of individual birds. An increase in monthly ranges during October was associated with covey formation.